Human Leukocyte Antigen Class II Alleles (DQB1 and DRB1) as Predictors for Response to Interferon Therapy in HCV Genotype 4 - Shaker, Olfat (Hindawi Publishing Corporation, 2013)
Human leukocyte antigens class II play an important role in immune response against HCV. We investigated whether HLA class II alleles influence susceptibility to HCV infection and response to interferon therapy. HLA-DRB1 and -DQB1 loci were genotyped using PCR-SSO Luminex technology. According to our regimen, 41 (66%) of patients achieved sustained virological response to combined treatment of IFN and ribavirin. Frequencies of DQB1∗0313 allele and DRB1∗04-DRB1∗11, DQB1∗0204-DQB1∗0313, DQB1∗0309-DQB1∗0313, and DQB1∗0313-DQB1∗0319 haplotypes were significantly more frequent in nonresponders than in responders. In contrast, DQB1∗02, DQB1∗06, DRB1∗13, and DRB1∗15 alleles were significantly more frequent in responders than in nonresponders. Similarly, DRB1∗1301, DRB1∗1361, and DRB1∗1369 alleles and DRB1∗1301-DRB1∗1328, DRB1∗1301-DRB1∗1361, DRB1∗1301-DRB1∗1369, DRB1∗1328-DRB1∗1361, and DRB1∗1328-DRB1∗1369 haplotypes were significantly found only in responders. Some alleles and linkages showed significantly different distributions between patient and healthy groups. These alleles may be used as predictors for response to treatment or to susceptibility to HCV infection in the Egyptian population.